THE ACCOUNTING OF ENVIRONMENTAL MANAGEMENT ISSUES IN THE PROCESS OF HARMFUL ENTERPRISES RESTRUCTURING - Mamchuk, I. V. (Science and Transport Progress, 2009)
In this article the account of ecological management issues during conduction of restructuring an ecologically harmful enterprise is considered. In the implementation of ecological management it is required to take into account an ecological passport, which allows analyzing in detail the ecological situation taking place at an enterprise. The mechanism of ecological management during the process of restructuring is considered.